RIPASA versus Alvarado score in the assessment of suspected appendicitis in children: a prospective study - Tülin Öztaş; Muhammet Asena (SpringerOpen, 2021)
Abstract Background Diagnosis of acute appendicitis remains a problem in children with right lower quadrant pain. Challenging diagnosis and fears of missing an inflamed appendix may lead to a negative appendectomy. Many scoring systems have been developed to reduce ambiguities in the diagnosis of appendicitis. Alvarado is one of the most commonly used scoring methods in pediatric patients. The RIPASA score is considered to be a better diagnostic scoring method in adults compared to Alvarado. The present study aims to compare RIPASA and Alvarado scoring systems in determining the possibility of acute appendicitis in children with right lower quadrant pain. This study included 179 consecutive pediatric patients who were referred to pediatric surgery with suspicion of acute appendicitis. The cut-off value was >7.5 for the RIPASA score vs. ≥7 for the Alvarado score. The possibility of appendicitis was divided into three groups for the Alvarado score and four groups for the RIPASA score. Results In this study, 158 of 179 patients were operated on. In 140 of the operated patients, the diagnosis of appendicitis was confirmed by histopathology. The negative appendectomy rate was 11.4%. Specificity and negative predictive value of RIPASA score were higher than those of Alvarado (p<0.001). No difference was found between the two scores concerning sensitivity, positive predictive value, and the area under the receiver operator characteristics curve (p>0.05). Conclusion The RIPASA scoring system can be used as an alternative to the Alvarado scoring system in the management of patients with right lower quadrant pain in emergency services and pediatric outpatient clinics. With the use of the RIPASA score, more patients with a low likelihood of appendicitis can be detected and further contributed to the reduction of the negative appendectomy rate.